Toxicity profile and treatment delays in NOPHO ALL2008—comparing adults and children with Philadelphia chromosome‐negative acute lymphoblastic leukemia. (24th April 2015) - Toft, Nina; Birgens, Henrik; Abrahamsson, Jonas; Griškevičius, Laimonas; Hallböök, Helene; Heyman, Mats; Klausen, Tobias Wirenfeldt; Jónsson, Ólafur Gísli; Palk, Katrin; Pruunsild, Kaie; Quist‐Paulsen, Petter; Vaitkeviciene, Goda; et al.
Abstract: Objectives: Cure rates improve when adolescents and young adults with acute lymphoblastic leukemia (ALL) are treated according to pediatric protocols. Assumed risks of toxicities and associated delays in treatment have played a role in setting upper age limits. The aim of this study was to examine the toxicity profile and treatment delays in NOPHO ALL2008 comparing children and adults. Methods: We collected information on 19 treatment‐related toxicities, systematically captured at 3‐month intervals throughout therapy, and time intervals between 12 consecutive treatment phases for 1076 patients aged 1–45 yrs treated according to the Nordic/Baltic ALL2008 protocol. Results: No adults died during induction. The duration of induction therapy and postinduction treatment phases did not differ between children and adults, except for patients 18–45 yrs being significantly delayed during two of nine high‐risk blocks (median number of days for patients 1–9, 10–17, and 18–45 yrs; the glucocorticosteroid/antimetabolite‐based block B1: 24, 26, and 29 d, respectively, P  = 0.001, and Block 5 (in most cases also a B block): 29, 29, and 37 d, respectively, P  = 0.02). A higher incidence of thrombosis with increasing age was found; highest odds ratio 5.4 (95% CI: (2.6;11.0)) for patients 15–17 yrs compared with children 1–9 yrs ( P  < 0.0001). Risk of avascular osteonecrosis was related to age with the highest OR for patients 10–14 yrs (OR = 10.4 (95% CI: (4.4;24.9)), P  < 0.0001). Conclusion: Adults followed and tolerated the NOPHO ALL2008 protocol virtually as well as children, although thrombosis and avascular osteonecrosis was most common among adolescents.